2011
DOI: 10.1515/bmc.2011.039
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes

Abstract: Here, we review the history, morphology, immunohistochemical phenotype, and presumptive roles of a new type of interstitial tissue cells, formerly called interstitial Cajal-like cells (ICLC) and by 2010 named 'telocytes' (TC). Many different techniques have been used to characterize TC and provide their unequivocal identification: (i) in vitro, cultures and isolated cells; (ii) in situ, fixed specimens examined by light and fluorescence microscopy, transmission (TEM) and scanning electron microscopy, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 58 publications
5
104
0
Order By: Relevance
“…They were not searched then for the CD34 expression. It was documented that, in human chorial villi, some TCs are CD34-positive, some are c-kit-positive [15,41]. Here a CD34-positive but c-kit-negative phenotype was found.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…They were not searched then for the CD34 expression. It was documented that, in human chorial villi, some TCs are CD34-positive, some are c-kit-positive [15,41]. Here a CD34-positive but c-kit-negative phenotype was found.…”
Section: Discussionmentioning
confidence: 98%
“…In 2010 the Romanian and Italian researchers renamed these cells from ICLCs to telocytes (TCs), their processes, long of "tens-up to hundreds of [micro]m", being named telopodes [31]. It was unequivocally stated that only transmission electron microscopy (TEM) "allows sure identification of telocytes, evaluation of the cell-tocell interrelationships, and a detailed description of the telopodes" [15]. This attitude was kept until 2014 when it was reinforced that "the features of telocytes are obvious only by transmission electron microscopy" [42].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TC, a particular identified type of stromal cell, has been identified morphologically by a small cell body and specific long prolongations called Telopodes (Tp) alternating thin segments (podomers) with dilations (podoms) [3]. TCs have been described in various organs and tissues, such as spleen [4], skin [5], esophagus [6], parotid gland [7], salivary glands [8], endocardium [9], bone marrow [10], pleura [11], vasculature [12], lung [13], duodenum [14], liver [15], eye [16], cardiac valves [17], uterus [18], et al Although TCs were also identified in large arteries [19], whether TCs exist in large veins was not yet reported. Here, the ultrastructural features of TCs in inferior vena cava were, for the first time, clarified under transmission electron microscope (TEM).…”
Section: Introductionmentioning
confidence: 99%